Integrating ESG Principles in MSME Management: A Qualitative Study of Governance and Accountability in Banten, Indonesia - Pramono, Tias; Nugroho, Yunianto Agung; Waruwu, Hatoli; Fauji, Ahmad; Jainuri, Jainuri (International Journal of Social and Management Studies, 2026)
The integration of Environmental, Social, and Governance (ESG) principles has increasingly been promoted as a pathway toward sustainable and accountable business practices. However, empirical understanding of how ESG principles are interpreted and implemented within micro, small, and medium enterprises (MSMEs) remains limited, particularly in developing economies. This study aims to explore how ESG principles are understood, operationalized, and embedded in governance and accountability practices among MSMEs in Banten Province, Indonesia. Adopting a qualitative and interpretive research design, the study draws on in-depth interviews, non-participant observations, and document analysis involving 24 participants, consisting of MSME owners, managers, and supporting institutional stakeholders. The findings reveal that ESG integration within MSMEs is largely implicit, fragmented, and highly context-dependent. While most participants lack formal familiarity with ESG as a comprehensive framework, many engage in practices aligned with its social and ethical dimensions, driven primarily by personal values, community norms, and relational trust. Governance practices are predominantly informal and centralized in owner-managers, with ethical leadership serving as the main mechanism shaping accountability rather than formal structures or standardized reporting systems. Financial accountability remains operational in nature, social accountability is relationally grounded, and environmental accountability is largely compliance-oriented. Key drivers of ESG integration include owner values, ethical orientation, and external pressures from markets and regulations, whereas major barriers consist of resource limitations, conceptual complexity of ESG frameworks, and fragmented institutional support. The study highlights that ESG implementation in MSMEs constitutes a socially embedded governance process rather than a formal compliance exercise. By providing qualitative evidence from an underexplored regional context, this research contributes to ESG and MSME governance literature and offers policy-relevant insights for developing adaptive, context-sensitive ESG frameworks suitable for small enterprises in emerging economies.